Triterpenoids isolated from the aerial parts of Buxus latistyla Gagnep. - Vo, Quoc Hung; Huynh, Thuy Vi; Doan, Ngoc Minh Thao; Huynh, Thi Bich Nguyet; Nguyen, Thi Minh Hieu; Doan, Thi Nhat Le (Tạp chí Y Dược Huế, 2023)
Background: Buxus latistyla Gagnep. (Buxaceae) has been used as a remedy for treating malaria, haemoptysis, amoebic dysentery etc. However, its chemical constituents are still unknown. Thus, the aim of this study was to identify phytochemicals isolated from this plant. Materials and method: Aerial parts of B. latistyla were collected from Quang Tri province. Pure compounds were isolated using the combination of chromatographic methods. Structures of isolated compounds were identified by analyzing spectral data of nuclear magnetic resonance as well as by comparing with reported data. Results & Conclusion: Five triterpenes were isolated and identified including lupeol (1), lupenone (2), betulin (3), 20(29)-lupene-2α,3α-diol (4), 20(29)-lupene-2α,3α ,28-triol (5). This is the first report about those phytochemicals of B. latistyla collected in Vietnam.